Large-Scale Perturbations of Magnetohydrodynamic Regimes Linear and Weakly Nonlinear Stability Theory - Zheligovsky, Vladislav; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
New developments for hydrodynamical dynamo theory have been spurred by recent evidence of self-sustained dynamo activity in laboratory experiments with liquid metals. The emphasis in the present volume is on the introduction of powerful mathematical techniques required to tackle modern multiscale analysis of continous systems and there application to a number of realistic model geometries of increasing complexity. This introductory and self-contained research monograph summarizes the theoretical state-of-the-art to which the author has made pioneering contributions.
Introduction -- Large-scale Passive Scalar Transport -- Steady-flow Dynamos -- Time-periodic Flow Dynamos -- Convective Plan-form Dynamos in a Layer -- Linear Stability of Steady MHD States to Large-scale Perturbations -- Weakly Nonlinear Stability of MHD Regimes -- Forced Hydromagnetic Thermal Convection: Weakly Nonlinear Stability to Large-scale Perturbation -- Free Hydromagnetic Thermal Convection: Weakly Nonlinear Stability to Large-scale Perturbations -- Magnetic Field Generation by Large-amplitude Flows With an Internal Scale in an Axisymmetric Volume. One Azimuthal Fast Variable -- Magnetic Field Generation by Large-amplitude Flows With an Internal Scale in a Sphere. Three Fast Variables -- General Conclusions and Perspectives -- References -- Appendix. Regimes of Free Hydromagnetic Thermal Convection, Symmetric About a Vertical Axis.
Keywords: Geography; Physical geography; Mathematical geography; Mathematical physics; Earth Sciences; Geophysics/Geodesy.; Classical Continuum Physics; Mathematical Applications in Earth Sciences; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Plasma Physics; Mathematical Methods in Physics